2017
DOI: 10.22159/ajpcr.2017.v10i9.19925
|View full text |Cite
|
Sign up to set email alerts
|

Study and Design of Portable Antimicrobial Water Filter

Abstract: Objective: This study was conducted to design a portable antimicrobial water filter which is both economic and easy to use.Methods: A prototype following the designing of the water filter was constructed. Layers of sand, cloth, activated charcoal, and cotton containing compartments were built for carrying out water analysis.Results: Most probable number index of Vellore Institute of Technology lake water was compared with that of filtered water. Complete water analysis was done, and the sand filter layer was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Extensive efforts have been made to reclaim and utilize these lands by rearing freshwater (food and ornamental) and brackishwater species. Among ornamental fish species, Koi carp and goldfish have also been successfully cultured in the inland saline waters of Punjab (Sharma et al 2017 andBhatt et al 2018) with regard to stress responses in terms of physiological changes. It has been observed that black molly ornamental fish can tolerate salinity, when maintained in inland saline waters for a short time period.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive efforts have been made to reclaim and utilize these lands by rearing freshwater (food and ornamental) and brackishwater species. Among ornamental fish species, Koi carp and goldfish have also been successfully cultured in the inland saline waters of Punjab (Sharma et al 2017 andBhatt et al 2018) with regard to stress responses in terms of physiological changes. It has been observed that black molly ornamental fish can tolerate salinity, when maintained in inland saline waters for a short time period.…”
Section: Resultsmentioning
confidence: 99%
“…When layered, its very fine texture helps to remove larger impurities like algae, as well as waterborne viruses, according to the National Drinking Water Clearinghouse. This makes diatomaceous earth-based water filters popular for recreational uses like swimming pools [11].…”
Section: Captivity-solution-productmentioning
confidence: 99%
“…More than 1.2 billion people have no access to clean drinking water [1]. Additionally, 1.8 billion people drinking water from sources susceptible to fecal contamination results in the death of approx.…”
Section: Introductionmentioning
confidence: 99%